Analisis Bibit Kelapa Sawit (Elaeis guineensis Jacq) Tercekam Kekeringan Terhadap Pemberian Fungi Mikoriza Arbuskula (FMA) Pada Pre Nursery - Hardiyanti, Lidya Sri; Kasim, Musliar; Dwipa, Indra (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2025)
This study is about the analysis of oil palm seedlings (Elaeis guineensis Jacq) stressed by drought against the administration of arbuscular mycorrhizal fungi (AMF) in pre nursery. This study aims to determine the effect of AMF on morphophysiology and biochemistry of oil palm seedling growth in pre nursery. This research was conducted at the UPT experimental garden (upper land), Faculty of Agriculture, Andalas University, Padang with an altitude of ±200 meters above sea level (masl). Observation of root colonization and proline accumulation tests were conducted at the Plant Physiology Laboratory, Faculty of Agriculture, Andalas University, Padang. The study was conducted from June to September 2024. The design used was a Completely Randomized Design (CRD) consisting of 2 factors, the first factor was the level of drought stress 4 treatment levels, namely field capacity (100, 75, 50 and 25%), the second factor was the dose of AMF 2 treatment levels, namely (10 grams/seedling, 15 grams/seedling). The data were analyzed statistically using the F test at a significance level of 5%, if the calculated F was greater than the F table, then continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The results of this study indicate that there is an interaction between field capacity treatment and AMF dose on the growth of oil palm seedlings, in observing proline accumulation test. The AMF dose of 10 grams showed the best results for all observation variables. The field capacity of 75% showed the best results for all observation variables.